C-Reactive Protein Levels in Children with Acute Bronchiolitis - Hasan M. Isa; Abdulrahman D. Mohroofi; Fatema N. Alkhan; Asma Z. Hasan; Mariam M. Alkubisi; Sana S. Alhewaizem; Sara I. Khalifa; Noora G. Alromaihi (International Journal of Pediatrics)
Background and Objectives. Acute bronchiolitis is a common respiratory disease in children. C-reactive protein (CRP) is an indicator of bacterial coinfection. This study is aimed at assessing the frequency of elevated CRP in children with acute bronchiolitis and at comparing the clinical characteristics, laboratory and radiological findings, antibiotics use, and outcome according to CRP levels. Material and Methods. We retrospectively reviewed medical records of children with acute bronchiolitis admitted to Pediatric Department, Salmaniya Medical Complex, Bahrain, in 2019-2020. Demographic, clinical, laboratory and radiological data, and outcomes were collected. Patients with high CRP were compared with those with normal levels. Results. Of 287 patients, 229 (79.2%) were included. 132 (57.6%) were males. Median presentation age was 3.7 (interquartile range (IQR), 1.27-12.33) months. Median CRP level was 10.4 (IQR, 2.8-35.1) mg/L. CRP was high in 167 (72.9%) patients. 17.6% (33/187 patients) had confirmed bacterial coinfection. Respiratory syncytial virus (RSV) was detected in 84 (36.7%) patients. Mean CRP level was higher in RSV-negative compared to RSV-positive patients, 31.3±44.3 versus 21.5±27.7 mg/L, respectively (P=0.042). Respiratory viral serology profile was positive in 34.7% (17/49 patients). 66.9% (107/160 patients) had positive chest X-ray. Antibiotics were used in 78.1% (179/227 patients). Thirteen (5.7%) patients required intensive care, five (2.2%) had surgical intervention, four (1.8%) required endotracheal intubation, and four (1.8%) died. Patients with high CRP were older at presentation (P<0.0001) and had more fever (P<0.0001) and cough (P=0.002), but lower hemoglobin level (P<0.0001) compared to those with normal CRP. Fever (P=0.016) and hemoglobin level (P=0.002) were independent factors. Conclusion. Most children with acute bronchiolitis had high rate of elevated CRP values that did not correlate with the rate of bacterial coinfection. High CRP levels were found in older children, those presented with more fever and cough, and had a lower hemoglobin level despite that those factors were previously reported to be associated with disease severity and bacterial coinfection. This study also showed a high overall rate of antibiotic prescriptions in mostly viral disease.